Relação entre a regulação emocional Up-Regulation e Down Regulation em uma tarefa atencional com distratores emocionais - Neves, Jayston W. J. Soares (2018)
The attentional demand for visual stimuli can alter the emotional impact of a situation, just as emotional visual stimuli can interfere with attention. Many factors may influence this interaction, among them, emotional regulation. The objective of this study was to investigate whether distracting emotional stimuli are capable of interfering in the performance of tasks with high attention engagement. In order to do so, discrimination tests were carried out in the orientation between two bars presented bilaterally in the periphery of the visual field (equal or different orientation), whose degree of difficulty depended on the difference in orientation of the same. At the same time, a neutral or negative emotional central figure was presented between the bars, and a valence judgment task (neutral or negative). Tasks were randomized in their order of presentation. Emotion Regulation Profile - Br was also used to evaluate the predominant mode of emotional regulation. It was characterized as descriptive, comparative, correlational, transversal nature of ex post facto research. Participants (n = 135) responded to the inclusion and exclusion tools for the study: socio-demographic questionnaire, Beck Inventory for Depression (BDI-II) and Beck Anxiety Inventory (BAI). The results indicated that the negative emotional distractor stimuli influenced the average hit rate in the most difficult task, which required a greater attentional engagement in the valence judgment. The data suggest that emotional stimuli are privileged in the dispute for attention resources.